SURVEY ON THE INCIDENCE OF SESAMIA INFERENS (WALKER) IN MAIZE IN GUNTUR AND KRISHNA DISTRICTS OF ANDHRA PRADESH - K. ANIL KUMAR*, T. MADHUMATHI, D.V. SAI RAM KUMAR, N. RAJ KUMAR and SK. NAFEEZ UMAR (The Journal of Research ANGRAU, 2023)
The cumulative results of roving survey was conducted during (rabi 2017-18 and 2018-19) inmaize growing mandals of Guntur and Krishna districts for recording Sesamia inferens infestation infarmer fields.The results showed that Narasaraopet mandal recorded the least infestation by S.inferens in terms of percentage leaf infestation (18.28), dead heart percentage (15.16), stem tunnelinglength (2.66 cm) and found less no. of larvae (0.39 plant-1), no. of pupae (0.22 plant-1) and Battiprolumandal recorded the least number of exit holes (0.48 plant-1). While, Ponnur mandal recorded thehighest percent leaf infestation (28.05) with stem tunneling length (5.71 cm).In Krishna district,Veerullapadu mandal recorded the least infestation of maize by S. inferens in terms of percent leafinfestation (15.33), dead heart percentage (12.97), stem tunneling length (2.10 cm) and found lessno. of larvae (0.24 plant-1), no. of pupae (0.18plant-1) and no. of exit holes (0.17 plant-1). Highestpercentage leaf infestation (24.28) and dead heart percentage (21.26) was recorded from Mylavarammandal;highest tunnel length (3.81 cm) from Musunnuru mandal. In case of Guntur district, highestnumber of spiders were recorded in Battiprolu (2.42) and least in Narasaraopet (1.39), while highestnumber of coccinellids were recorded in Ponnuru (4.74) and least in Battiprolu (3.54) mandals.Furthermore, more number of spiders (2.69) were recorded in Mylavaram mandal, more number ofcoccinellids (7.12) in Musunnuru mandal, and least number of spiders (1.18) and least number ofcoccinellids (2.58) in Veerullapadu mandal of Krishna district.